Peran Sistem OPAC Sebagai Katalog Online dalam Efisiensi Penyediaan Informasi di Era Pandemi - Aulya Azki Fikriya Luthfi; Bachrul Ilmi (Central Library of Universitas Sebelas Maret, 2021)
Since the COVID-19 outbreak was declared to have hit most countries, various changes in habits and new life orders have been implemented for people in the hemisphere, including Indonesia, in all fields. In an effort to break the chain of spread of the COVID-19 virus, the Indonesian government issued regulations ranging from online school learning to working from home (WFH) for workers. The impact given is felt in all circles and aspects of society. One of them is the library. Activities in the library should be minimized more than usual due to the existing social restriction policies. Libraries must be able to innovate so that the provision of information can continue efficiently even though there are social restrictions that limit the community's space for movement. The online catalog is one means that supports the efficiency of providing information in the library. It is the purpose of this paper to provide an understanding of the role online catalogs play in providing information during the pandemic. The research method used is a qualitative approach. The data collection technique used is a literature study, so that secondary data can be obtained. The results of the study show that online catalogs as information searchers can be a facility that is able to facilitate librarians in providing information as well as users in searching for information availability in the pandemic era where activities outside the home are limited.